Sun Exposure and Protection Habits in Pediatric Patients with a History of Malignancy. - Yael Levy-Shraga; Rinat Cohen; Michal Ben Ami; Yonatan Yeshayahu; Vered Temam; Dalit Modan-Moses (PLoS ONE, 2015)
Survivors of childhood cancer are at high risk for developing non-melanoma skin cancer and therefore are firmly advised to avoid or minimize sun exposure and adopt skin protection measures. We aimed to compare sun exposure and protection habits in a cohort of pediatric patients with a history of malignancy to those of healthy controls.Case-control study of 143 pediatric patients with a history of malignancy (aged 11.2±4.6 y, Male = 68, mean interval from diagnosis 4.4±3.8 y) and 150 healthy controls (aged 10.4±4.8 y, Male = 67). Sun exposure and protection habits were assessed using validated questionnaires.Patients and controls reported similar sun exposure time during weekdays (94±82 minutes/day vs. 81±65 minutes/day; p = 0.83), while during weekends patients spent significantly less time outside compared to controls (103±85 minutes/day vs. 124±87 minutes/day; p = 0.02). Time elapsed from diagnosis positively correlated with time spent outside both during weekdays (r = 0.194, p = 0.02) and weekends (r = 0.217, p = 0.01), and there was a step-up in sun exposure starting three years after diagnosis. There was no significant difference regarding composite sun protection score between patients and controls. Age was positively correlated with number of sunburns per year and sun exposure for the purpose of tanning, and was negatively correlated with the use of sun protection measures.Although childhood cancer survivors are firmly instructed to adopt sun protection habits, the adherence to these instructions is incomplete, and more attention should be paid to improve these habits throughout their lives. Since sunlight avoidance may results in vitamin D deficiency, dietary supplementation will likely be needed.